2020
DOI: 10.1155/2020/9385097
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and Electroconductivity Properties of Graphite Tailings Concrete

Abstract: is paper investigated the mechanical and electroconductivity properties of graphite tailings concrete, in which the graphite tailings are replaced as sand. e results showed that the concentration of graphite tailings has an important influence on the mechanical, electroconductivity, and material properties of concrete. Finally, a new model for calculating the relationship between compressive strength and electrical resistivity based on the grey correlation method was obtained for providing a theoretical basis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 41 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…There has been rare research on GT environment-friendly concrete. Liu et al [37][38][39][40][41][42] prepared GT concrete with high electrical conductivity, frost resistance, and mechanical properties. Kathirvel, P. et al [43] suggested that the optimal mechanical properties and durability can be obtained when GT are replaced by 40% volume content of sand.…”
Section: Comparison Of Gt and Sand Mesoscopic Picturesmentioning
confidence: 99%
“…There has been rare research on GT environment-friendly concrete. Liu et al [37][38][39][40][41][42] prepared GT concrete with high electrical conductivity, frost resistance, and mechanical properties. Kathirvel, P. et al [43] suggested that the optimal mechanical properties and durability can be obtained when GT are replaced by 40% volume content of sand.…”
Section: Comparison Of Gt and Sand Mesoscopic Picturesmentioning
confidence: 99%
“…Chloride penetrates concrete, destroys steel passive flm, and causes steel corrosion [23][24][25]. In recent years, Hong-Bo et al [26][27][28][29][30] studied the infuence of graphite tailings on the properties of cementbased materials and concrete blocks. Te results show that the mechanical properties of cement-based materials can be improved by adding an appropriate amount of graphite tailings.…”
Section: Introductionmentioning
confidence: 99%
“…Simultaneously, as a nonrenewable resource, which plays a vital role in modern economic development. Consequently, the amount of graphite mined increases each year, leading to a considerable production of low-grade graphite ore and graphite tailings [ 1 ]. The flotation process is commonly used in the production of graphite, with each ton of graphite requiring 100 tons of water and 10 tons of raw graphite ore on average.…”
Section: Introductionmentioning
confidence: 99%